2012
DOI: 10.1039/c2ee03592h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for enhanced oxygen reduction kinetics at the (La,Sr)CoO3−δ/(La,Sr)2CoO4+δ hetero-interface

Abstract: The recently reported fast oxygen reduction kinetics at the interface of (La,Sr)CoO 3-δ (LSC 113 ) and (La,Sr) 2 CoO 4+δ (LSC 214 ) phases opened up new questions for the potential role of dissimilar interfaces in advanced cathodes for solid oxide fuel cells (SOFCs). Using first-principles based calculations in the framework of density functional theory, we quantitatively probed the possible mechanisms that govern the oxygen reduction activity enhancement at this hetero-interface as a model system. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 63 publications
8
118
1
Order By: Relevance
“…Anisotropic oxygen diffusion along the 2 main crystallographic directions (ab plane and c-axis) were measured for LSC25 between 250 and 500ºC in both the transversal and longitudinal configurations (Figure 9(a) ). The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 large difference in oxygen diffusivity between the two orientations in this composition is consistent with the previous computational predictions which showed an interstitial oxygen transport via an interstitialcy mechanism within the ab plane 34,44,47,48 . …”
Section: Anisotropic Diffusion Kinetics Of Oxygen Quantified Bysupporting
confidence: 94%
See 2 more Smart Citations
“…Anisotropic oxygen diffusion along the 2 main crystallographic directions (ab plane and c-axis) were measured for LSC25 between 250 and 500ºC in both the transversal and longitudinal configurations (Figure 9(a) ). The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 large difference in oxygen diffusivity between the two orientations in this composition is consistent with the previous computational predictions which showed an interstitial oxygen transport via an interstitialcy mechanism within the ab plane 34,44,47,48 . …”
Section: Anisotropic Diffusion Kinetics Of Oxygen Quantified Bysupporting
confidence: 94%
“…In ref. 34 An anisotropy (temperature dependent) of circa 2 orders of magnitude is apparent in the tracer diffusion coefficients, D*, shown in Figure 1 (a). The anistropy for the surface exchange coefficients, k*, shown in Figure 1 (b) is less strong than that for diffusion.…”
Section: Previous Results On Anisotropic Diffusion and Surface Reactimentioning
confidence: 98%
See 1 more Smart Citation
“…Sase et al confi rmed that used epitaxial (La,Sr) CoO 3− δ (LSC113) on (La,Sr) 2 CoO 4− δ (LSC214) gave ORRs more than three orders of magnitude faster, at 500 °C, than were observed by using only the single-phase LSC113 surface. [33][34][35][36][37] Several research groups have investigated this enhancement of ORR kinetics caused by the heterostructured LSC113/LSC214 system to attempt to explain the mechanisms involved and the wileyonlinelibrary.com causes of the increased reaction rate. There have been some disagreements between the hypotheses and mechanisms that have been proposed; however, the theory that interfacial regions contribute to the enhanced ORR kinetics is now regarded as being established.…”
Section: Introductionmentioning
confidence: 98%
“…One study interprets the experimentally observed increased oxygen exchange rate at such interfaces [68] as caused mainly by a redistribution of Sr from the perovskite to the interface region coupled with a respective strong local increase of the oxygen vacancy concentration. Another investigation focuses more on the strain caused at the hetero interface leading to increased oxygen vacancy mobility [69]. There is also an idea that the transition state structure of the perovskite may play an important role in the course of the vacancy diffusion [70][71][72][73].…”
Section: A Balance Between Two Effectsmentioning
confidence: 99%